2018
DOI: 10.3847/1538-4357/aaae03
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Magnetic Rayleigh–Taylor Instability into the Outer Solar Corona and Low Interplanetary Space

Abstract: We analyze the observations from Solar TErrestrial RElations Observatory (STEREO)-A&B/COR-1 of an eruptive prominence in the intermediate corona on 7 June 2011 at 08:45 UT, which consists of magnetic Rayleigh-Taylor (MRT) unstable plasma segments. Its upper northward segment shows spatio-temporal evolution of MRT instability in form of finger structures upto the outer corona and low inter-planetary space. Using method of Dolei et al.(2014), It is estimated that the density in each bright finger is greater than… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Properties of filament blobs, some of which were falling back to the Sun, were investigated by Innes et al (2012), Williams et al (2013), Carlyle et al (2014), and Thompson & Young (2016); the impacts themselves by Gilbert et al (2013), Reale et al (2014), and Innes et al (2016). Bright filament ejecta in the outer corona were studied by Susino et al (2015), Wood et al (2016), and Mishra et al (2018). However, none of these studies dealt with the initial and impulsive phases of the eruption, and the accompanying reconnection in the low corona at these times.…”
Section: The Filament Eruption Of 2011 June 07mentioning
confidence: 99%
“…Properties of filament blobs, some of which were falling back to the Sun, were investigated by Innes et al (2012), Williams et al (2013), Carlyle et al (2014), and Thompson & Young (2016); the impacts themselves by Gilbert et al (2013), Reale et al (2014), and Innes et al (2016). Bright filament ejecta in the outer corona were studied by Susino et al (2015), Wood et al (2016), and Mishra et al (2018). However, none of these studies dealt with the initial and impulsive phases of the eruption, and the accompanying reconnection in the low corona at these times.…”
Section: The Filament Eruption Of 2011 June 07mentioning
confidence: 99%
“…A prominence eruption occurred on June 7 th 2011 as observed by Solar TErrestrial RElations Observatory (STEREO). It is observed that the eruptive prominence is magnetic Rayleigh-Taylor unstable from the inner corona to the low interplanetary space (Innes et al 2012;Carlyle et al 2014;Mishra et al 2018). We demonstrate that the eruptive prominence eruption moves in form of the MRT unstable plasma spikes into the inter-planetary space reaching upto 1 A.U.…”
Section: Introductionmentioning
confidence: 77%
“…7: Solutions of the dispersion relation for a given growth time in terms of magnetic field inclination (θ) and propagation direction (α), for two observed prominence plumes. Observational data has been taken from (Mishra & Srivastava 2019).…”
Section: Discussionmentioning
confidence: 99%